Agro-biological traits of common millet (Panicum miliaceum L.) genotypes in regular and stubble crop - Sikora Vladimir; Filipović Vladimir; Berenji Janoš; Popović Vera (Ratarstvo i Povrtarstvo, 2013)
Agro-biological traits of common millet (Panicum miliaceum L.) genotypes were studied on experimental lots of the Institute of Field and Vegetable Crops in Bački Petrovac, Serbia in 2009 and 2010. The study included 16 genotypes of millet grown and used in selection programs in Serbia and abroad. Crops in trials were based on regular and stubble crops. A significant variability appeared during and at the end of growing season in the number of days from emergence to earing of some genotypes of millet, plant height, grain yield, 1000-grain weight and test weight of the test material, and it can be used as a good basis for further work on breeding and improvement of common millet. Cluster analysis identified genotypes with high performance for yield per plant, but also good stability of other studied parameters. Studies have shown that the genetic factor had significant effect on realized values of all tested traits. The difference between the yield of millet in regular and stubble crops was also statistically significant. Out of 9 varieties and lines of millet, 3 of them achieved a higher yield in stubble crops. From the point of agro-biological traits, 2010 was more favourable for the production of millet.